Stakeholder Views on the Potential Benefits and Feasibility of an Equestrian Industry-Specific Health, Safety and Welfare Management System - Meredith Chapman; Kate Fenner; Matthew J. W. Thomas; Kirrilly Thompson (Animals)
With the growth of the equestrian industry, risk exposure and the obligation to maintain the health, safety, and welfare of humans and horses remain front and centre. As there has been no apparent reduction in non-fatal human horse-related injuries, we asked industry stakeholders to discuss their current management and risk mitigation practices and highlight potential barriers to improving these processes. Semi-structured interviews were conducted with 20 stakeholders from Australian equestrian work- (n = 9) and non-work- (n = 11) related organisations to determine the potential benefits and feasibility of adopting an industry-specific health, safety, and welfare (HSW) management system. The International Organisation for Standardisation (ISO) 45001:2018 Occupational Health and Safety Management framework, often used by high-risk industries, guided deductive data coding. Most participants preferred formal HSW management systems and supported improvements in their current HSW practices. Industry gaps included (1) lack of training, education material, and competency; (2) social licence to operate (SLO) regarding horse welfare; and (3) management of and resistance to change. Industry barriers included (1) lack of good governance and (2) poor safety culture related to tradition and human behaviours. Most stakeholders sought further collaboration, HSW guidance materials, and national industry representation opportunities, with supporting the concept of an adaptable industry-specific HSW management system. Further multi-sector equestrian stakeholder engagement is recommended to determine the feasibility of adopting and modifying (ISO) 45001:2018 as a suitable equestrian industry-specific HSW management system.